2018
DOI: 10.1039/c8ta06319b
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism behind freezing-induced chemical crosslinking in ice-templated cellulose nanofibril aerogels

Abstract: The underlying mechanism related to freeze-induced crosslinking of aldehyde-containing cellulose nanofibrils (CNFs) has been investigated, and the critical parameters behind this process have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 45 publications
4
61
0
2
Order By: Relevance
“…Consequently, these samples could resist the structural stress caused by the destructive capillary forces during evaporation; whereas the ones prepared without any salt addition largely collapsed. It is worth noting that ice crystals have been shown to push CNFs close enough toward each other to establish chemical contact in a previous study …”
Section: Aerogels From Cellulose Nanofibers and Sodium Alginatementioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, these samples could resist the structural stress caused by the destructive capillary forces during evaporation; whereas the ones prepared without any salt addition largely collapsed. It is worth noting that ice crystals have been shown to push CNFs close enough toward each other to establish chemical contact in a previous study …”
Section: Aerogels From Cellulose Nanofibers and Sodium Alginatementioning
confidence: 90%
“…This is commonly achieved by crosslinking the fibrillar structure, either in the dry or the wet state, with covalent inter‐fibrillar bonds such as ether, urethane, ester, or hemiacetal linkages . Recent studies demonstrated the preparation of wet‐stable aerogels from dialdehyde CNFs by using a simple freezing, thawing, and solvent exchange procedure . Thanks to the absence of critical point drying and freeze‐drying, this process could presumably be fairly easily made continuous and meet industrial requirements both in terms of energy consumption and production rate.…”
Section: Introductionmentioning
confidence: 99%
“… 303 This freeze-linking process applies to cross-linker-free systems, as in the ice driven packing of sodium periodate-oxidized CNFs that were made wet-stable (then suitable for application or functionalization in liquid media, e.g., layer-by-layer assembly of multilayers) 950 via hemiacetal cross-links between the introduced aldehyde groups and their native hydroxyls. 951 , 952 …”
Section: Formation Of Multiscale Architecturesmentioning
confidence: 99%
“…The capillary forces between the particles of a porous material affect its density. A decrease in capillary forces decreases the density of the material, resulting in lighter materials [93]. Freeze-drying avoids capillary forces; for example, freezing at −18 • C and subsequent freeze-drying produced the lightest cellulose material (density 0.0002 g/cm 3 ) from a 0.1% cellulose nanofibril hydrogel [94].…”
Section: Capillary Forcesmentioning
confidence: 99%